COVID-19 and Personality: A Cross-Sectional Multicenter Study of the Relationship Between Personality Factors and COVID-19-Related Impacts, Concerns, and Behaviors - AL-Omiri, Mahmoud K.; Alzoubi, Ibrahim A.; Al Nazeh, Abdullah A.; Alomiri, Abdallah K.; Maswady, Mohannad N.; Lynch, Edward (Frontiers in Psychiatry, 2021)
Background: This cross sectional observational study aimed to evaluate COVID-19 related precautions to avoid COVID-19 infection, distress and behavioural changes, fears and concerns, and effects on opinions and believe among participants from different backgrounds. Also, to identify the relationships between personality factors and COVID-19 related changes and impacts. Methods: 1319 participants (744 females and 575 males, mean age ±SD= 32.7 ±11.6 years) completed a three-section survey collecting data regarding demographic information, personality factors (using NEO Five Factor Inventory (NEO-FFI)), and COVID-19 related issues (using VAS scale). Findings: COVID-19 was associated with changes related to precautions to avoid COVID-19 infection, distress and behavioural changes, fears and concerns, and effects on opinions and believe (P< .05). Higher neuroticism scores were associated with more negative COVID-19 related changes and impacts (P< .05). Higher extraversion, agreeableness, and conscientiousness scores were associated with more acceptance of COVID-19 containment measures as well as less COVID-19 related changes and impacts (P< .05). Conclusions: Personality factors were associated with COVID-19 related impacts. These findings demonstrate the importance of the relationship between personality factors and COVID-19 related changes.